THE QUEST OF INDONESIAN MUSLIM IDENTITY: Debates on Veiling from the 1920s to 1940s (State Islamic University (UIN) of Sunan Ampel Surabaya, 2010)
This paper undertakes a debate of wearing veil for Muslim women among Indonesian Muslim scholars and role of modernist Muslims in propagating it in the early twentieth century. It shows that, the modernist Muslims’ propagation on veil had massively started in the early twentieth century trough printed media and encountered fierce responses from others. In addition, the debate itself was influenced by similar trends in Middle Eastern countries, especially Egypt, which became the reference of Islamic current issues at the time. Because of the uncompromising propagation on veil, the debate not only stimulated polemics but also invited physical violence, which was proven to be unproductive for the campaign. Therefore, the spread of veil among Indonesian Muslim during those decades in Java was not significant with only few Muslim women who were affiliated to Modernist organization such as Muhammadiyah and Persis wore veils. The debate itself was not merely a contentious religious debate but also cultural debate which shows the quest of identity as being Indonesian and being Muslim at the same time. The issue of cutting off from Western cultural domination also spiced up the veiling debate.